The geochemistry and origin of xenoliths from the Roberts Victor Mine - Hatton, Christopher John (Department of Geological Sciences, 2024)
The results of an investigation into the geochemistry of xenoliths from the Roberts Victor mine are reported. 750 nodules were examined in hand specimen at the Roberts Victor mine, and in accordance with previous observations greater than 95% are eclogite xenoliths. The paucity of peridotite nodules is attributed to selective sampling by the kimberlite, and to the preferential abrasion of the more readily altered peridotites. 250 samples were selected for further study in slabbed section. Mineral analyses by electron microprobe of 100 samples, and whole rock analyses by X-ray fluorescence of 40 samples were carried out. Orthopyroxene bearing eclogites (garnet websterites) constitute a significant portion of the eclogite suite, and orthopyroxene plays an important role in the evolution of the Roberts Victor eclogites. Three categories of inhomogeneous eclogites, clinopyroxene-megacryst-bearing eclogites, inhomogeneous kyanite eclogites and chrome-rich eclogites were examined in detail. (i) Megacryst-bearing eclogites originated by crystallisation of clinopyroxene megacrysts within volatile-rich portions of an eclogite magma and the subsequent entrapment of the megacryst within biminerallic eclogite. (ii) Inhomogeneous kyanite eclogites consist of biminerallic eclogite enclosing a kyanite eclogite zone of markedly different mineral and whole rock chemistry. The kyanite eclogite zone most likely originated by liquid immiscibility. (iii) Most chrome-rich eclogites examined exhibit marked variation in chemistry over very short distances. These variations have been attributed to fluctuations in volatile content during crystallisation, disequilibrium partial melting of garnet lherzolite and to the preservation of a diffusion gradient between two bodies of different composition. The diverse peridotite suite at Roberts Victor includes dunite, wehrlite, harzburgite, garnet harzburgite, lherzolite and garnet lherzolite. A connecting link between peridotite and eclogite is represented by an altered garnet lherzolite in which a thin layer of biminerallic eclogite is preserved on one edge. Detailed studies of the mineral chemistry of an eclogite containing both diamond and graphite indicate that this rock equilibrated at 40 to 45 kbar in the temperature range 1000 to 11 so 0 c. Diamond and graphite a'."e thought to have formed by the reduction of CO2 , introduced together with Ti, Kand S, during the melting of garnet lherzolite to produce the eclogitic magma from which the rock crystallised. The Roberts Victor eclogite suite is thought to have originated by volatile induced partial melting of garnet lherzolite. The diversity of the eclogite suite is related to the relative importance of the volatile input and the thermal input during partial melting, with high volatile, low temperature melting leading to the production of heterogeneous, rapidly crystallised eclogite bodies (type II eclogites) and low volatile, higher temperature melting leading to the production of a larger, relatively homogeneous eclogite body (type I eclogite).